Addressing biopiracy through the BBNJ agreement's marine genetic resources framework: Reflections from the clarion-clipperton zone for Indonesia’s future - Nasywa Intan Ramadhanty (Privietlab, 2026)
Marine Genetic Resources (MGRs) located in Areas Beyond National Jurisdiction (ABNJ) have long been subject to asymmetric appropriation, with a single corporation controlling 47% of patented marine genetic sequences and entities from just ten countries holding 98% of such patents (Blasiak et al., 2018). This article examines how the United Nations Convention on the Law of the Sea (UNCLOS) 1982 facilitates this appropriation through structural legal gaps, how the BBNJ Agreement (2023) addresses them, and the implications for Indonesia. Employing a normative juridical methodology with statutory and conceptual approaches, the study finds that the UNCLOS definition of